2022
DOI: 10.1002/ente.202200290
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Function Upgradation of All‐Inorganic CsPbIBr2 Perovskite Film by Doping an Ionic Additive for Carbon–Electrode‐Based Solar Cells

Abstract: All‐inorganic CsPbIBr2 perovskite solar cells (PSCs) recently demonstrated great superiority for application in tandem and semitransparent photovoltaics because of their excellent phase stability. However, compared to state‐of‐the‐art PSCs, the inferior film quality is harmful for the photovoltaic performance improvement. Herein, a novel ionic additive, tetrabutylammonium hexafluorophosphate (TBAPF6), is employed to improve the all‐inorganic CsPbIBr2 perovskite film quality and passivate detrimental defects. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The ideality factor of the optimal HTAB‐1 device is closer to 1 under open‐circuit conditions (1.34 vs 2.04 in Figure 3c) and short‐circuit (0.996 vs 0.987 in Figure S10, Supporting Information) than the pristine device, further ensuring the reduction of bimolecular recombination and trap‐assisted recombination by plotting the dependence of J SC and V OC on light intensity. [ 48 ] Furthermore, as shown in Figure 3d, the built‐in potential ( V bi ) was conducted from the classical Mott–Schottky (M–S) relation under dark condition. The HTAB‐1 device exhibits a larger slope (dashed lines) and a 40 mV higher V bi of 1.35 V than that of the pristine device (1.31 V) evidently demonstrating the increased interfacial driving force of charge carrier separation and drift, which, in turn, delivers an improved V OC due to the accelerated interfacial charge transfer at the CsPbIBr 2 /carbon surface of the HTAB‐1 device.…”
Section: Resultsmentioning
confidence: 99%
“…The ideality factor of the optimal HTAB‐1 device is closer to 1 under open‐circuit conditions (1.34 vs 2.04 in Figure 3c) and short‐circuit (0.996 vs 0.987 in Figure S10, Supporting Information) than the pristine device, further ensuring the reduction of bimolecular recombination and trap‐assisted recombination by plotting the dependence of J SC and V OC on light intensity. [ 48 ] Furthermore, as shown in Figure 3d, the built‐in potential ( V bi ) was conducted from the classical Mott–Schottky (M–S) relation under dark condition. The HTAB‐1 device exhibits a larger slope (dashed lines) and a 40 mV higher V bi of 1.35 V than that of the pristine device (1.31 V) evidently demonstrating the increased interfacial driving force of charge carrier separation and drift, which, in turn, delivers an improved V OC due to the accelerated interfacial charge transfer at the CsPbIBr 2 /carbon surface of the HTAB‐1 device.…”
Section: Resultsmentioning
confidence: 99%
“…In an investigation, tetrabutylammonium hexafluorophosphate (TBAPF 6 ) was explored as an additive. [89] The results indicate that the TBAPF 6 benefited from regulating the crystallization process, resulting in an enlarged perovskite grain size and larger surface coverage. In addition, TBA + cations could passivate surface defects via electrostatic interaction.…”
Section: Additive Engineeringmentioning
confidence: 93%
“…Cho et al added the ammonium halide salt M-P chloride to form a chloride-rich intermediate phase in the precursor, retarding the nucleation rate and enlarging the grain Fig. 14 Chemical structures of MAB, BAFa, 104 MAAc, phenylurea, 105,143 DMII, 106 OMIMCl, 107 TBAPF 6 , 108 [C1CNmim]Cl, [C3CNmim]Cl and [(C3CN) 2 im]Cl. 110 size from B250 nm to B470 nm.…”
Section: Grain Size Enlargementmentioning
confidence: 99%
“…107 Zheng et al reported that with an IL additive TBAPF 6 , PF 6 − anions could partially substitute the halide ions and chelate Pb 2+ cations, which was beneficial to slow down the crystal growth. 108 In addition, the alkyl chain in TBA + may also alter the crystallization, enabling an enlarged perovskite grain size with improved surface coverage. Biberger studied in situ perovskite growth after solution-dropping, observing the fast formation of solvent-complex phases, which were gradually transformed to perovskite phases.…”
Section: Improvement Of Crystalline Propertymentioning
confidence: 99%